Aplicación de una metodología de desarrollo turístico local basada en el capital social, en la comunidad San Diego de Rodeopamba, parroquia Mulalillo, cantón Salcedo, provincia Cotopaxi en el año 2021 - Velastegui Coque, Alex Vinicio (2021)
The community of San Diego de Rodeopamba is a clear example or a bad attempt at tourism development that despite having received help from public entities such as tourist signage, formation of a dance group, infrastructure for its headquarters (kitchen, lodging) with the objective of encouraging the tourist economic reactivation has not been successful. The objective of this work is to achieve a local tourist development using a methodology based on the strengthening of social capital, on this occasion the community is considered as a fundamental part and not the material that the community needs for this process, its representative was identified, socialized the intervention, identified its actors, a survey of its tourist and cultural potential was carried out, a permanent tourism team or committee was created with community members who live full time in the community, trained in areas of knowledge of tourism activity such as administration, guidance, gastronomy, recreational activities, marketing, sales, etc. As a next step, the tourist packages were created with the members of the community tourism team or committee, in this way a tourist product is obtained that is the community, which is constantly monitored to ensure its evolution, has a tourist product. With this work, a functional and non-superficial tourism product is achieved with the participation of the community that is prepared to receive tourists with a quality offer in all areas.